Performance characteristics of multi-evaporator transcritical CO 2 refrigeration cycles with hybrid compression/ejection - Sarkar J. (My University, 2025)
The theoretical analyses and optimization studies of two novel multi-evaporator transcritical CO2 refrigeration systems using constant pressure mixing ejector are presented in this article. Comparisons of novel hybrid compression-ejection CO2 cycles, based on coefficient of performance (COP) improvement over conventional cycle and other optimum parameters, are also done for various operating conditions. Study shows that the cycle performance is dependent on allocation of evaporator cooling capacities for both cycles. The optimum discharge pressure for both cycle layouts compared to corresponding basic cycle reduces by the use of ejection-compression. For both cycle layouts, the effect of gas cooler exit temperature on COP improvement is negligible, whereas the COP improvement at optimum condition increases with the increase in temperature difference between evaporators. Results reveal that the CYC1 is superior due to lower discharge pressure and significantly higher COP improvement (maximum of 38.1 per cent for CYC1 whereas 21.4 per cent for CYC2 at optimum condition for the studied ranges).